ANALISIS PENGARUH ATRIBUT TABUNGAN, MUTU TABUNGAN DAN PROMOSI PENJUALAN TERHADAP CITRA PERUSAHAAN DALAM MENINGKATKAN MINAT MENABUNG NASABAH TABUNGAN (Studi kasus pada Bank Jateng cabang kordinator Semarang) - Pratiwi, Dani; Soesanto, Harry (Faculty of Economics and Business Diponegoro University, 2016)
This study aims to analyze how much influence the product attribute, product quality and sales promotions to customers' interest in saving Bank Jateng Cabang Kordinator Semarang. This study also aims to analyze whether the variable image of the company is able to mediate variable product attribute, product quality and sales promotion of the interests of saving.The population used in this study are active customers who are conducting transactions at Bank Jateng Cabang Kordinator Semarang. Samples in this study of 100 respondents and the technique used is the technique of Non-probability sampling with accidental sampling approach (sampling by coincidence).From the analysis, the indicators in this study is valid and the variables are valid. The results showed that the variables attribute products, product quality and sales promotion has positive effect on the company's image. Then, the image variable positive effect on the company's interest in the customer Savings Bank Jateng Cabang KordinatorÂ Semarang.